Principles of macroeconomics Karl E. Case, Ray C. Fair, Sharon M. Oster - Case, Karl E. 1946-; Fair, Ray C. 1942-; Oster, Sharon M. 1948-2022 (Pearson, 2020)
This title is a Pearson Global Edition. The Editorial team at Pearson has worked closely with educators around the world to include content which is especially relevant to students outside the United States. For one-semester courses in the principles of macroeconomics. An introduction to the functioning of the economy and the power and breadth of economics Reviewers tell us that Case/Fair/Oster is one of the all-time bestselling principles of economics texts because they trust it to be clear, thorough, and complete. Readers of Principles of Macroeconomics, 13th Edition, Global Edition come